COVID-19 knowledge, perception, preventive measures, stigma, and mental health among healthcare workers in three sub-Saharan African countries: A Phone Survey - Assefa, Nega; Soura, Abdramane; Hemler, Elena C.; Korte, Michelle L.; Wang, Dongqing; Abdullahi, Yasir Y.; Lankoande, Bruno; Millogo, Ourohiré; Chukwu, Angela; Workneh, Firehiwot; Sié, Ali; Berhane, Yemane; et al. (The American journal of tropical medicine and hygiene, 2021)
ABSTRACT. The coronavirus disease 2019 (COVID-19) pandemic is an unprecedented public health crisis globally. Understanding healthcare providers’ (HCPs’) knowledge and perceptions of COVID-19 is crucial to identifying effective strategies to improve their ability to respond to the pandemic in sub-Saharan Africa. A phone-based survey of 900 HCPs in Burkina Faso, Ethiopia, and Nigeria (300 per country) was conducted to assess knowledge, perceptions, COVID-19 prevention measures, stigma, and mental health of HCPs. Modified Poisson regression models were used to evaluate predictors of knowledge, perceptions, and prevention measures; adjusted risk ratios (ARRs) and 95% confidence intervals (CIs) were calculated. Three-fourths of the HCPs had adequate knowledge, and over half had correct perceptions of risk and high levels of self-reported prevention measures. The majority of the HCPs (73.7%) reported self-perceived social stigma. There was relatively low prevalence of depression (6.6%), anxiety (6.6%), or psychological distress (18%). Compared with doctors, being a nurse was associated with lower levels of knowledge (ARR: 0.83; 95% CI: 0.77-0.90) and was also negatively associated with having correct perceptions toward COVID-19 (AOR: 0.82; 95% CI: 0.73-0.92). HCPs treating COVID-19 patients had higher likelihood of having high levels of prevention measures (AOR: 1.37; 95% CI: 1.23-1.53). Despite high levels of knowledge among HCPs in sub-Saharan Africa, there is a need to improve COVID-19 perceptions and compliance with prevention measures as well as address social stigma toward HCPs to better ensure their safety and prepare them to deliver health services.